1977
DOI: 10.1177/25.7.330728
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic orientation of cells.

Abstract: Chicken erythrocytes orient when caught in the confluence of two sheath-liquid streams. Preliminary results indicate that this phenomena might be used to align cells for morphologic analysis in flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…It has been concluded that an apparent bimodal DNA distribution in fixed acriflavine/Feulgen-stained bull sperm heads analysed in such a system, is due to an orientation artefact (Dean, Pinkel & Mendelson, 1978), perhaps analogous to that previously described by Loken, Parks & Herzenberg (1977) for the light scatter (size) artefact seen with chicken red blood cells (chicken RBC). Both of these artefacts can be by-passed or removed by the use of an appropriate nozzle which will control the orientation of flattened particles such as sperm heads or chicken RBC relative to the laser beam (Fulwyler, 1977 ;Stovel, Sweet & Herzenberg, 1978;Dean et al, 1978). As an alternative approach, distribution artefacts can be tested by sorting the population into its separate components and then reanalysing them independently: if an artefact is involved, each reanalysed peak will give a bimodal peak similar to that observed originally.…”
Section: Introductionmentioning
confidence: 90%
“…It has been concluded that an apparent bimodal DNA distribution in fixed acriflavine/Feulgen-stained bull sperm heads analysed in such a system, is due to an orientation artefact (Dean, Pinkel & Mendelson, 1978), perhaps analogous to that previously described by Loken, Parks & Herzenberg (1977) for the light scatter (size) artefact seen with chicken red blood cells (chicken RBC). Both of these artefacts can be by-passed or removed by the use of an appropriate nozzle which will control the orientation of flattened particles such as sperm heads or chicken RBC relative to the laser beam (Fulwyler, 1977 ;Stovel, Sweet & Herzenberg, 1978;Dean et al, 1978). As an alternative approach, distribution artefacts can be tested by sorting the population into its separate components and then reanalysing them independently: if an artefact is involved, each reanalysed peak will give a bimodal peak similar to that observed originally.…”
Section: Introductionmentioning
confidence: 90%
“…The higher the sample pressure the more cells have an opportunity to move laterally in the stream, causing a decrease in precision of hydrodynamic focusing, and consequently a drop in quality of the sample analysis, due to increases in the Coefficient of Variation of the peak values. The nozzle design is essential for obtaining laminar fluxes (Fulwyler 1977) in order to transport cells to the center of the stream: nozzle aperture should be narrow and perfectly calibrated (between 50 and 2,000 microns, depending on applications). This hydrodynamic focusing results from several stability developments (Steen 1990), and is used in most flow cytometers.…”
Section: Flow Cytometry Fundamentalsmentioning
confidence: 99%
“…After it was demonstrated that it is not possible to differentiate sex-specific markers by physical methods, Gledhill et al (1982) published the first experiments on flow cytometry on spermatozoa, which were followed by further technical adaptations to these specific cells (Fulwyler 1977, Dean et al 1978, Stovel et al 1978, Garner et al 1983, Johnson & Pinkel 1986, Johnson et al 1987a, 1987b, Johnson & Clarke 1988. The first pre-sexed offspring using this technique were born in 1988 (Morrell et al 1988).…”
Section: Sex Sorting Of Spermatozoa By Flow Cytometrymentioning
confidence: 99%